(untitled) (Scientific journal of the Fergana State University, 2023)
The article presents a comparative analysis of the features of interpretation of historical figures in relation to the image of Mashrab in Uzbek novels. The article highlights the stylistic diversity in the style of writers, their skills of influencing from historical sources.